Chemical Immersion Effects on Wear Property of Epoxy Reinforced Copper Powder Composites - Raghad Hamid Hilal (Journal of Techniques)
In this research, the effect of chemical solutions: (sulfuric acid H2SO4, sodium hydroxide NaOH) at (5 M) and distilled water were studied on some mechanical properties. Especially the wear resistance by pin-on-disk and hardness properties for neat epoxy composite and (epoxy - copper powder) composite. That has been prepared by hand mixing (weight ratio = 20%). The samples were immersed in these chemical solutions for different periods (7, 14, and 30) days. Then the hardness by the Shore D method was measured before and after immersion of the samples in acidic, neutral, and alkali solutions.  Whereas the hardness was measured by the Vickers method for the wear disk.  Wear rate was measured for all samples. The results showed that the neat epoxy composite was more affected by the alkali solution, followed neutral solution, and then the acidic solution by increasing the radius of wear disk (3, 5, 7, 9, and 11) cm, t= 15 min. and the load 5 N. In contrast to the composite material that was more affected by the alkali solution than the acid, neutral solution.